Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Instalasi Gizi RSUP Dr. Mohammad Hoesin Palembang - Anggreany Hustia (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The research was to determine the effect of motivation and discipline on employee performances. The sample was 56 employees of the Nutrition Installation at Dr. Mohammad Hoesin Palembang. Type of research was associative.The primary and secondary data used to know the information about the company and respondence with shared the questionnaire about work motivation and discipline. The method of data analysis used qualitative method which was then quantified. The techinique of data analysis used multiple linear regression analysis. The results showed that it is true that work discipline and motivation are very important aspects in influencing the performance of employees in Nutrition Installation at RSUP Dr. Mohammad Hoesin Palembang based on the F test and t test with conviction level of 90%.